2014
DOI: 10.1088/0256-307x/31/3/030701
|View full text |Cite
|
Sign up to set email alerts
|

Coating Qualities Evaluation for Alkali-Metal Atomic Vapor Cells Based on Frustrated Total Internal Reflection

Abstract: To realize accurate measurement of coating thickness and surface reliefs for alkali-metal vapor cells, a measurement method based on frustrated total internal reflection (FTIR) is proposed. Firstly, the phenomenon of frustrated total internal reflection and the theory of coating thickness measurement based on FTIR are introduced. Then a coating thickness measuring system based on FTIR is established and the coating thickness measuring experiment is carried out. Next, surface reliefs are obtained by analyzing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…If the noises above are optimized by technology means, the sensitivity of the hybrid optical pumping SERF atomic magnetometer approaches to the ultimate sensitivity, which is also helpful to study the atomic spin gyroscope [48][49][50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…If the noises above are optimized by technology means, the sensitivity of the hybrid optical pumping SERF atomic magnetometer approaches to the ultimate sensitivity, which is also helpful to study the atomic spin gyroscope [48][49][50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicated that the coatings could adsorb alkali-metal atoms. Quan et al 13) accurately measured the coating thickness and surface reliefs for alkali-metal vapor cells by using frustrated total internal reflection (FTIR). They found that the FTIR method can precisely measure the coating thickness with an accuracy greater than 2 nm, which can satisfy the evaluation criteria for the assessment of coatings on alkali-metal vapor cells.…”
Section: Introductionmentioning
confidence: 99%